2022 President’s Award Recipient: Kelly Byram, MS, MBA, ELS - Burton, Katrina (AMWA Journal, 2022)
The recipient of the President's Award is selected by the AMWA President, and each year this award is bestowed upon a member of AMWA who has made distinctive contributions to the association at the chapter or national level.